If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(t+1)=13
We move all terms to the left:
-3(t+1)-(13)=0
We multiply parentheses
-3t-3-13=0
We add all the numbers together, and all the variables
-3t-16=0
We move all terms containing t to the left, all other terms to the right
-3t=16
t=16/-3
t=-5+1/3
| 3(2n+4)=53 | | (4x+12)/(3)|=4 | | (3x-2)/5=2x-3 | | (D^3-3D+4)y=0 | | 3.7g=-4.45 | | -9x-8=7x+40 | | 5r*2r^2+r=3 | | 5r*2r^2+r=1 | | (X+139)(x+57)=180 | | 3x+12+6=5x-5+1 | | 3.8g=-104.13 | | 3x+12+6=15x-5+1 | | 16a=0.096 | | 3x+12+6=15x-5+ | | 24=4x-8+2x | | Y-11=-1/2(x/ | | Y=|x|+2 | | -4(-5t-4)=2(10t+8) | | y+25y=0 | | 3x^2+4x^2=1000 | | 4x+6/10=8 | | 54.82x2.15=117.863 | | 4x+6÷10=8 | | X^2-14x+30=9 | | 3(2p+1)+9p+2=140 | | 2x+1)+3=3(x-1) | | 7x^2+36x+1=-4 | | 2x/9+4x/3=14 | | 290t^2+5t+30=0 | | 10x+10=1x+1 | | 2x+x+25=0 | | 12x+9x-6+2=8x+2-6 |